2000
DOI: 10.1098/rspb.2000.1129
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among the Nymphalidae (Lepidoptera) inferred from partial sequences of thewinglessgene

Abstract: A cladistic analysis was performed on a 378 bp region of the wingless gene from 103 nymphalid species and three pierid outgroups in order to infer higher level patterns of relationship among nymphalid subfamilies and tribes. Although the data are highly homoplastic, in many instances the most parsimonious cladograms corroborate traditionally recognized groups. The results suggest that this short gene region provides a useful source of data for phylogenetic inference, provided that adequate e¡ort is made to sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
1
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 41 publications
9
98
1
6
Order By: Relevance
“…In this study, the ML and BI phylogenetic analyses based on the mitogenomic data of the nine available nymphalids, including that of P. sulpitia and other unpublished species, revealed the following relationships: (Danainae + ((Libytheinae + ((Satyrinae + Calinaginae) + (Apaturinae + (Heliconiinae + Limenitidinae) + Nymphalinae))))) with high support values (Fig. 4), which is congruent with those reported by Wahlberg et al (2003Wahlberg et al ( , 2005 and Brower (2000). In conclusion, the complete mitogenome of P. sulpitia harbored nearly the same characters as those of other nymphalids.…”
Section: Phylogenetic Analysissupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, the ML and BI phylogenetic analyses based on the mitogenomic data of the nine available nymphalids, including that of P. sulpitia and other unpublished species, revealed the following relationships: (Danainae + ((Libytheinae + ((Satyrinae + Calinaginae) + (Apaturinae + (Heliconiinae + Limenitidinae) + Nymphalinae))))) with high support values (Fig. 4), which is congruent with those reported by Wahlberg et al (2003Wahlberg et al ( , 2005 and Brower (2000). In conclusion, the complete mitogenome of P. sulpitia harbored nearly the same characters as those of other nymphalids.…”
Section: Phylogenetic Analysissupporting
confidence: 76%
“…For example, Freitas & Brown (2004) conducted a cladistic analysis of Nymphalidae based on immature and adult morphological characters, and the results showed that Limenitidinae is sister to the grouping of (Apaturinae + (Calinaginae + Satyrinae)), exclusive of the remaining nymphalidae taxa (Freitas & Brown, 2004). However, phylogenetic analyses based on molecular sequence data have convincingly suggested that Limenitidinae is the sister group of Heliconiinae (Brower, 2000;Wahlberg et al, 2003Wahlberg et al, , 2005Zhang et al, 2008). In this study, the ML and BI phylogenetic analyses based on the mitogenomic data of the nine available nymphalids, including that of P. sulpitia and other unpublished species, revealed the following relationships: (Danainae + ((Libytheinae + ((Satyrinae + Calinaginae) + (Apaturinae + (Heliconiinae + Limenitidinae) + Nymphalinae))))) with high support values (Fig.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than assuming progression from a simple solution to a more optically sophisticated one, we can then look for evidence to support such a trend, and identify other evolutionary trends. While sections of this tree have been verified by different morphological and molecular phylogenetic studies (Harvey 1991;Parsons 1996;Ackery et al 1999;Morinaka et al 1999;Brower 2000;Reed & Sperling 2001;Wahlberg et al 2003;Freitas & Brown 2004;Hauser et al 2005), no single study covers all the species. Thus, the tree represents a fairly conservative estimate of the phylogeny.…”
Section: Evolutionary Relationshipsmentioning
confidence: 99%
“…These studies have used both morphological (Freitas & Brown 2004) and molecular characters (Brower 2000, Wahlberg et al 2003, Peña et al 2006 to ind further support for clades, and more recently employing a total evidence approach in order to obtain more consistent and coherent hypotheses (Wahlberg et al 2005, 2009, Peña & Wahlberg 2008. These studies yielded similar results with morphological characters of adults and immatures (Freitas & Brown 2004) and with DNA sequences of mitochondrial (COI) and nuclear (EF-1α and wingless) (Brower 2000, Wahlberg et al 2003 genes, inding a "satyroid" clade made up of Charaxinae, Calinaginae, Satyrinae and Morphinae. Also, combining morphological characters of adults and molecular data provides further support for this clade (Wahlberg et al 2005), but its relationship to the rest of Nymphalidae remains unresolved.…”
Section: Satyrinae In Nymphalidaementioning
confidence: 99%